2012
DOI: 10.1007/s13197-012-0784-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of selective production media for enhanced production of xylanases in submerged fermentation by Thielaviopsis basicola MTCC 1467 using L16 orthogonal array

Abstract: Enzymes have been the centre of attention for researchers/industrialists worldwide due to their wide range of physiological, analytical, food/feed and industrial based applications. Among the enzymes explored for industrial applications, xylanases play an instrumental role in food/feed, textile/detergent, paper and biorefinery based application sectors. This study deals with the statistical optimization of xylanase production by Thielaviopsis basicola MTCC 1467 under submerged fermentation conditions using ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…The results indicated a total significant increment of 208.09 and 192.59% when compared with the conventional unoptimized xylanase synthesis by both A. niger L3 and T. longibrachiatum L2, respectively. These results compared well with previous reports of xylanase production that were optimized using Taguchi method where 277%, 161.5%, 41.9 and 10.24% higher enzyme yields were obtained (Lakshmi et al 2009;Rani et al 2014;Mandal et al 2015). The increase can be claimed to have resulted from the interactions and relations among the various factors (Mandal et al 2015).…”
Section: Optimization Of Xylanase Production Through Taguchi Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The results indicated a total significant increment of 208.09 and 192.59% when compared with the conventional unoptimized xylanase synthesis by both A. niger L3 and T. longibrachiatum L2, respectively. These results compared well with previous reports of xylanase production that were optimized using Taguchi method where 277%, 161.5%, 41.9 and 10.24% higher enzyme yields were obtained (Lakshmi et al 2009;Rani et al 2014;Mandal et al 2015). The increase can be claimed to have resulted from the interactions and relations among the various factors (Mandal et al 2015).…”
Section: Optimization Of Xylanase Production Through Taguchi Methodssupporting
confidence: 91%
“…Such carbon source or substrate concentration dependent enzyme production has been reported in diverse xylanase synthesizing microbial strains (Oliveira et al 2006;Kapoor et al 2008). Also, Rani et al (2014) reported that carbon source (rice straw) produced the greatest effect in the production of xylanase.…”
Section: Optimization Of the Production Of Xylanasesmentioning
confidence: 68%
See 3 more Smart Citations